Gel polymer electrolyte, preparation method thereof and battery

By introducing modified polymers into gel polymer electrolytes, combined with specific monomer structure and molar ratio design, the problem of difficult to take into account both the mechanical strength and electrochemical properties of gel polymer electrolytes is solved, and efficient battery cycle stability is achieved.

CN119920965APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311432310.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing gel polymer electrolytes are difficult to take into account both mechanical strength and electrochemical properties, and are easily poked by lithium crystal branches, affecting the cycle stability of the battery.

Method used

A gel polymer electrolyte is provided whose polymer body contains a matrix polymer and a modified polymer, which improves mechanical strength and electrochemical properties through a specific monomer structure and molar ratio design.

Benefits of technology

High fracture stress and room temperature ion conductivity are achieved, the electrochemical window is expanded, and the cycle stability of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920965A_ABST
    Figure CN119920965A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer and electrochemical energy storage, and discloses a gel polymer electrolyte, a preparation method thereof and a battery. The gel polymer electrolyte comprises a polymer main body and an electrolyte salt solution impregnated in the polymer main body, the polymer main body contains a matrix polymer and a modified polymer; wherein the matrix polymer contains a structural unit A as shown in a formula (I) # imgabs 0 # and a structural unit B as shown in a formula (II) # imgabs 1 #; the molar ratio of the structural unit A to the structural unit B is 1: (0.01-25). The gel polymer electrolyte provided by the invention has excellent mechanical strength, is not easily punctured by lithium crystal dendrites, and can bring better cycle stability to energy storage devices such as batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer and electrochemical energy storage, and in particular to a gel polymer electrolyte and a preparation method thereof and a battery. Background Art

[0002] Solid electrolytes have attracted much attention due to their high safety, good thermal stability, high energy density and good compatibility. However, among them, oxide solid electrolytes are limited by their poor mechanical properties and other problems. When in direct contact with lithium alloys or lithium metals, they are very likely to react and produce lithium dendrites, which penetrate the electrolyte and cause short circuits, thereby affecting the cycle stability. At present, the mechanical properties of solid electrolytes can be improved by adding additives, but this increases costs and limits the application of solid electrolytes in the field of all-solid-state batteries. The present invention provides a gel polymer electrolyte to effectively improve the cycle stability of batteries using solid electrolytes. Summary of the invention

[0003] The present invention aims to solve the problem that the existing gel polymer electrolyte is difficult to achieve both mechanical strength and electrochemical performance, and the gel polymer electrolyte is easily punctured by lithium dendrites, thereby affecting the cycle stability of the battery, and provides a gel polymer electrolyte and a preparation method thereof and a battery.

[0004] In order to achieve the above-mentioned object, the present invention provides a gel polymer electrolyte in a first aspect, comprising: a polymer body, and an electrolyte salt solution impregnated in the polymer body; the polymer body contains a matrix polymer and a modified polymer;

[0005] Wherein, the base polymer contains a structural unit A represented by formula (I) and a structural unit B represented by formula (II);

[0006]

[0007] In formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C4 alkyl group; R3 and R4 are each independently selected from a C1-C4 alkyl group;

[0008] In formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C4 alkyl group;

[0009] The molar ratio of structural unit A:structural unit B is 1:(0.01-25).

[0010] A second aspect of the present invention provides a method for preparing a gel polymer electrolyte, comprising:

[0011] (1) polymerizing monomer A' and monomer B' to obtain a matrix polymer;

[0012] (2) blending the base polymer and the modified polymer to form a film to obtain a polymer film;

[0013] (3) plasticizing and swelling the polymer film with an electrolyte salt solution to obtain a gel polymer electrolyte;

[0014] Wherein, the monomer A' has a structure shown in formula (III), and the monomer B' has a structural unit shown in formula (IV);

[0015]

[0016] In formula (III), R1' and R2' are each independently selected from hydrogen or a C1-C4 alkyl group; R3' and R4' are each independently selected from a C1-C4 alkyl group;

[0017] In formula (IV), R5', R6', and R7' are each independently selected from hydrogen or a C1-C4 alkyl group;

[0018] The molar ratio of the monomer A':monomer B' is 1:(0.01-25).

[0019] The third aspect of the present invention provides a gel polymer electrolyte prepared by the method described in the second aspect.

[0020] A fourth aspect of the present invention provides a battery comprising the gel polymer electrolyte described in the second aspect or the third aspect.

[0021] Through the above technical solution, the gel polymer electrolyte provided by the present invention can better balance mechanical strength and electrochemical performance, and is characterized by having a higher fracture stress, high room temperature ionic conductivity, and a wide electrochemical window. Assembling batteries and other energy storage devices using the gel polymer electrolyte can bring better cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 This is the infrared spectrum of the matrix polymer in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0026] In a first aspect, the present invention provides a gel polymer electrolyte, comprising: a polymer body, and an electrolyte salt solution impregnated in the polymer body; the polymer body contains a matrix polymer and a modified polymer;

[0027] Wherein, the base polymer contains a structural unit A represented by formula (I) and a structural unit B represented by formula (II);

[0028]

[0029] In formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C4 alkyl group; R3 and R4 are each independently selected from a C1-C4 alkyl group;

[0030] In formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C4 alkyl group;

[0031] The molar ratio of structural unit A:structural unit B is 1:(0.01-25).

[0032] The gel polymer electrolyte provided by the present invention comprises a matrix polymer containing a structural unit A represented by the above formula (I) and a structural unit B represented by the above formula (II), and the molar ratio of the structural unit A to the structural unit B is 1:(0.01-25). On this basis, a modified polymer is introduced for blending and modification, so that the gel polymer electrolyte has suitable mechanical strength and can bring better cycle stability to energy storage devices such as batteries.

[0033] According to the present invention, preferably, in the structural unit A shown in formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C2 alkyl group; R3 and R4 are each independently selected from a C1-C2 alkyl group; in the structural unit B shown in formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C2 alkyl group. The structural units A and B having this preferred composition can enable the matrix polymer to better balance mechanical strength and electrochemical performance.

[0034] According to the present invention, the structural unit A and the structural unit B satisfy the above-mentioned proportional relationship. Preferably, the molar ratio of the structural unit A:structural unit B is 1:(0.5-1), which can enable the matrix polymer to better balance mechanical strength and electrochemical performance.

[0035] According to the present invention, in the polymer body, the base polymer and the modified polymer are physically blended. Preferably, the weight ratio of the base polymer to the modified polymer is 1:(0.1-10). Further preferably, the weight ratio of the base polymer to the modified polymer is 1:(0.5-1).

[0036] According to the present invention, the modified polymer can improve the film-forming property, thermal stability, mechanical properties, liquid absorption capacity, and ionic conductivity of the polymer body. Preferably, the modified polymer can be selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyterephthalates, polyethers, polyimides, polyacrylonitrile, nylon, and cellulose. Further preferably, the modified polymer is selected from at least one of polyolefins, polysulfonates, and polyimides.

[0037] According to the present invention, the polymer body of the gel polymer electrolyte can be a non-porous structure or a porous structure. When the polymer body is a non-porous structure, it has excellent mechanical strength. When the polymer body is a porous structure, it can have a higher liquid absorption rate while having good mechanical strength. Preferably, the pores contained in the polymer body have a pore size of 0.5-10 μm and a porosity of 10-85%, which can make the gel polymer electrolyte have better liquid absorption capacity and higher ionic conductivity.

[0038] In the present invention, the pore diameters of the pores contained in the polymer matrix are measured by scanning electron microscopy (SEM), and the porosity of the polymer matrix is ​​measured by mass method.

[0039] According to the present invention, in the gel polymer electrolyte, the electrolyte salt solution is impregnated in the polymer body as an electrolyte. The present invention has a wide range of electrolyte salt types in the electrolyte salt solution, and conventional selections in the art can be used, including but not limited to at least one of zinc salts, lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts and aluminum salts. For example, the electrolyte salt can be lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI) or lithium bisfluorosulfonyl imide (LIFSI), etc.

[0040] In the present invention, the type of solvent in the electrolyte salt solution is relatively broad, and conventional choices in the art can be used, including but not limited to water, carbonates, ethers, ionic liquids, etc. Preferably, the concentration of the salt in the electrolyte salt solution is 0.1-50 mol / L, wherein the salt refers to a metal ion compound.

[0041] The gel polymer electrolyte provided by the present invention has excellent mechanical strength, specifically high fracture stress, good interface stability, high room temperature ionic conductivity, and wide electrochemical window. It can be used in a variety of electrochemical energy storage systems, including but not limited to batteries (including secondary batteries), supercapacitors, etc., and can bring better cycle stability to the electrochemical energy storage system. The use of the gel polymer electrolyte provided by the present invention in lithium-ion batteries can make the lithium-ion batteries have a higher capacity retention rate.

[0042] In the present invention, the breaking stress is measured by an electronic multifunctional tensile tester.

[0043] According to a most preferred embodiment of the present invention, in the gel polymer electrolyte, in the structural unit A shown in the above formula (I), R1 and R2 are hydrogen, R3 and R4 are independently selected from C1-C2 alkyl groups; in the structural unit B shown in the above formula (II), R5, R6 and R7 are independently selected from hydrogen or methyl groups; the molar ratio of structural unit A: structural unit B is 1: (0.5-1). The gel polymer electrolyte of this preferred composition can better balance mechanical strength and electrochemical performance.

[0044] A second aspect of the present invention provides a method for preparing a gel polymer electrolyte, comprising:

[0045] (1) polymerizing monomer A' and monomer B' to obtain a matrix polymer;

[0046] (2) blending the base polymer and the modified polymer to form a film to obtain a polymer film;

[0047] (3) plasticizing and swelling the polymer film with an electrolyte salt solution to obtain a gel polymer electrolyte;

[0048] Wherein, the monomer A' has a structure shown in formula (III), and the monomer B' has a structural unit shown in formula (IV);

[0049]

[0050] In formula (III), R1' and R2' are each independently selected from hydrogen or a C1-C4 alkyl group; R3' and R4' are each independently selected from a C1-C4 alkyl group;

[0051] In formula (IV), R5', R6', and R7' are each independently selected from hydrogen or a C1-C4 alkyl group;

[0052] The molar ratio of the monomer A':monomer B' is 1:(0.01-25).

[0053] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (1), the monomer A' and the monomer B' are subjected to a free radical polymerization reaction in the presence of an initiator, so that the matrix polymer obtained by polymerization can have suitable mechanical strength.

[0054] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (1), for the monomer A' represented by formula (III), preferably, R1 ’ , R2 ’ Each is independently selected from hydrogen or C1-C2 alkyl; R3 ’ 、R4 ’ Each independently selected from a C1-C2 alkyl group; for the monomer B' represented by formula (IV), preferably, R5', R6', R7 ’ Each is independently selected from hydrogen or a C1-C2 alkyl group. The use of the above preferred monomers A' and B' can enable the matrix polymer to better balance mechanical strength and electrochemical performance.

[0055] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (1), the reaction system, type and amount of initiator used in the polymerization reaction are relatively loosely limited, and conventional olefin monomers can be used for free radical polymerization.

[0056] According to the present invention, in the method for preparing the gel polymer electrolyte, preferably, the solvent used in the polymerization reaction can be selected from at least one of N,N-dimethylformamide (DMF), toluene, xylene and dichloromethane, and more preferably N,N-dimethylformamide.

[0057] According to the present invention, in the preparation method of the gel polymer electrolyte, preferably, the initiator used in the polymerization reaction can be selected from at least one of benzoyl peroxide, diisopropylbenzene peroxide, azobisisobutyronitrile and azobisisoheptylnitrile, and more preferably azobisisobutyronitrile. Preferably, the molar ratio of the initiator: (monomer A'+monomer B') is 1: (5-20).

[0058] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (1), the polymerization reaction is carried out in an oxygen-free and water-free environment. Preferably, the polymerization reaction conditions include: a temperature of 50-90° C. and a time of 1-24 hours.

[0059] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (1), on the basis of satisfying the above-mentioned feeding molar ratio, preferably, the molar ratio of monomer A':monomer B' is 1:(0.5-1), so that the prepared matrix polymer can better balance mechanical strength and electrochemical performance.

[0060] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (2), the process and parameters used for the blending film are relatively broad, as long as the matrix polymer and the modified polymer can be blended to obtain a uniform polymer film.

[0061] In some embodiments of the present invention, the blending film-making method comprises:

[0062] (2-1) mixing the base polymer, the modified polymer and a solvent to obtain a polymer solution;

[0063] (2-2) The polymer solution is subjected to a film-forming treatment to obtain the polymer film.

[0064] According to the present invention, in step (2-1), the solvent is a polar solvent, which can be selected from at least one of water, acetone, carbonate, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), and dioxane.

[0065] According to the present invention, in step (2-1), preferably, the mixing temperature can be 50-90° C., which is conducive to obtaining a better mixing effect.

[0066] According to the present invention, in step (2-2), the film forming treatment method may include casting, coating, papermaking, hot pressing, screen printing, freeze drying, electrospinning, phase inversion, impregnation, foaming, in-situ polymerization, Bellcore method, etc. In the specific implementation, the devices and operating conditions known in the art can be used, and the present invention does not make any special limitation on this.

[0067] According to the present invention, in the method for preparing the gel polymer electrolyte, in step (2), the weight ratio of the matrix polymer to the modified polymer is 1:(0.1-10), preferably 1:(0.5-1).

[0068] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (2), the modified polymer is selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyester terephthalates, polyethers, polyimides, polyacrylonitrile, nylon and cellulose, preferably at least one of polyolefins, polysulfonates and polyimides.

[0069] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (3), the polymer film is immersed in the electrolyte salt solution, and the polymer film is plasticized and swelled so that the polymer film fully absorbs the electrolyte salt solution to obtain a gel polymer electrolyte.

[0070] According to the present invention, the type of electrolyte salt in the electrolyte salt solution is relatively broad, and conventional selections in the art can be adopted, including but not limited to at least one of zinc salt, lithium salt, sodium salt, potassium salt, calcium salt, magnesium salt and aluminum salt. For example, the electrolyte salt can be lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI) or lithium bisfluorosulfonyl imide (LIFSI), etc.

[0071] According to the present invention, the type of solvent in the electrolyte salt solution is relatively broad, and conventional selections in the art can be used, including but not limited to water, carbonates, ethers, ionic liquids, etc. Preferably, the concentration of the salt in the electrolyte salt solution is 0.1-50 mol / L, wherein the salt refers to a metal ion compound.

[0072] According to the present invention, in the preparation method of the gel polymer electrolyte, in step (3), preferably, the conditions for plasticizing and swelling include: temperature of 0-30° C., and time of 1 min-24 h.

[0073] The third aspect of the present invention provides a gel polymer electrolyte prepared by the method described in the second aspect.

[0074] According to the present invention, the composition and performance of the gel polymer electrolyte prepared by the method described in the second aspect are the same as those of the gel polymer electrolyte described in the first aspect of the present invention, and will not be described in detail herein.

[0075] A fourth aspect of the present invention provides a battery comprising the gel polymer electrolyte described in the second aspect or the third aspect.

[0076] The battery provided by the present invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the gel polymer electrolyte described in the second aspect or the third aspect of the present invention. Compared with batteries using conventional electrolytes, under the same conditions, the battery provided by the present invention can effectively tolerate lithium dendrites generated during the cycle and has significant advantages in cycle stability.

[0077] The battery provided by the present invention includes but is not limited to semi-solid-state lithium ion battery, semi-solid-state sodium ion battery, semi-solid-state lithium sulfur ion battery, etc. The use of the gel polymer electrolyte provided by the present invention in the lithium ion battery can make the ion battery have better cycle stability.

[0078] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.

[0079] Example 1

[0080] (1) Dry a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cool by vacuuming; replace nitrogen gas in the single-mouth bottle three times, and add 20 mL of ultra-dry DMF to the single-mouth bottle and bubble for 30 minutes; add azobisisobutyronitrile (AIBN) to the Shrek bottle, replace nitrogen gas three times, transfer the bubbled DMF to the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (styrene) to the Shrek bottle, wherein the molar ratio of monomer A':monomer B' is 1:1; the molar ratio of AIBN:(monomer A'+monomer B') is 1:15; bubble nitrogen gas through the above reaction system for 30 minutes, and then react at 80°C for 6 hours; after the reaction is completed, cool to room temperature, add the product system dropwise into deionized water, precipitate a white solid, filter by suction, take the filter cake and dissolve it in DMF, then add deionized water, filter by suction, and freeze-dry the filter cake to obtain a white solid (i.e., matrix polymer, denoted as M1);

[0081] The obtained matrix polymer was tested by infrared spectroscopy, and the results are shown in Figure 1 , Figure 1 It can be seen that at the wave number 2900cm -1 The -CH stretching vibration of -CH3 or -CH2 appears at the wave number 1721.8cm -1 -C=O stretching vibration appears at wave number 1650-1500cm -1 There is no peak at , and no C=C double bond exists, indicating that methyl methacrylate monomer and styrene monomer are successfully polymerized to obtain the matrix polymer;

[0082] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:1;

[0083] (2-1) mixing the above-mentioned matrix polymer and polyvinylidene fluoride (PVDF) with a solvent (DMF), and stirring at 60° C. for 3 h to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:1;

[0084] (2-2) Using a 500 μm coating applicator, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 1-5 μm, porosity of 55.5%);

[0085] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 12 h in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as P1).

[0086] Example 2

[0087] (1) Drying a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cooling by vacuum; replacing nitrogen gas in the single-mouth bottle three times, adding 20 mL of ultra-dry DMF into the single-mouth bottle, and bubbling for 30 minutes; adding azobisisobutyronitrile (AIBN) into the Shrek bottle, replacing nitrogen gas three times, transferring the above-bubbled DMF into the Shrek bottle, and then adding monomer A' (methyl methacrylate) and monomer B' (α-methylstyrene) into the Shrek bottle, wherein the molar ratio of monomer A':monomer B' is 1:0.5;

[0088] The molar ratio of AIBN: (monomer A' + monomer B') is 1:15; nitrogen gas is bubbled in the above reaction system for 30 minutes, and then the reaction is carried out at 80°C for 6 hours; after the reaction is completed, the product system is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, which is filtered by suction, and the filter cake is dissolved in DMF, and then deionized water is added, filtered by suction, and the filter cake is freeze-dried to obtain a white solid (i.e., the matrix polymer, denoted as M2);

[0089] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:0.5;

[0090] (2-1) mixing the above-mentioned base polymer and polyvinylidene fluoride with a solvent (DMF), and stirring at 60° C. for 24 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the base polymer to polyvinylidene fluoride is 1:1;

[0091] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 1-10 μm, porosity of 80%);

[0092] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 12 h in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as P2).

[0093] Example 3

[0094] (1) Drying a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cooling by vacuum; replacing nitrogen gas in the single-mouth bottle three times, and adding 20 mL of ultra-dry DMF to the single-mouth bottle, and bubbling for 30 minutes; adding azobisisobutyronitrile (AIBN) to the Shrek bottle, replacing nitrogen gas three times, and transferring the above-bubbled DMF to the Shrek bottle, and then adding monomer A' (methyl methacrylate) and monomer B' (styrene) to the Shrek bottle, wherein monomer A': monomer The molar ratio of monomer A' and monomer B' is 1:0.05; the molar ratio of AIBN: (monomer A' + monomer B') is 1:15; nitrogen gas is bubbled in the above reaction system for 30 minutes, and then reacted at 50°C for 24 hours; after the reaction is completed, it is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, which is filtered by suction, and the filter cake is dissolved in DMF, and then deionized water is added, filtered by suction, and the filter cake is freeze-dried to obtain a white solid (i.e., the matrix polymer, denoted as M3);

[0095] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:0.05;

[0096] (2-1) mixing the matrix polymer and polyvinylidene fluoride with a solvent (DMF), and stirring at 60° C. for 1 hour to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:0.1;

[0097] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 1-4 μm, porosity of 35%);

[0098] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 1 min in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as P3).

[0099] Example 4

[0100] (1) Dry a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cool by vacuum; replace nitrogen gas in the single-mouth bottle three times, and add 20 mL of ultra-dry DMF to the single-mouth bottle and bubble for 30 minutes; add azobisisobutyronitrile (AIBN) to the Shrek bottle, replace nitrogen gas three times, transfer the bubbled DMF to the Shrek bottle, and then add monomer A' (ethyl methacrylate) and monomer B' (styrene) to the Shrek bottle, wherein the molar ratio of monomer A':monomer B' is 1:5; the molar ratio of AIBN:(monomer A'+monomer B') is 1:10; bubble nitrogen gas through the above reaction system for 30 minutes, and then react at 90°C for 24 hours; after the reaction is completed, cool to room temperature, add the product system dropwise into deionized water, precipitate a white solid, filter by suction, take the filter cake and dissolve it in DMF, then add deionized water, filter by suction, and freeze-dry the filter cake to obtain a white solid (i.e., matrix polymer, denoted as M4);

[0101] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:5;

[0102] (2-1) mixing the matrix polymer and polyvinylidene fluoride with a solvent (DMF), and stirring at 60° C. for 3 h to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:10;

[0103] (2-2) Using a 500 μm coating applicator, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.5-2 μm, porosity of 25%);

[0104] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The gel polymer electrolyte was prepared by mixing LiPF6 solution (the solvent was ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a weight ratio of 1:1:1) for 24 hours to obtain a gel polymer electrolyte (denoted as P4).

[0105] Example 5

[0106] (1) Dry a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cool by vacuum; replace nitrogen gas in the single-mouth bottle three times, and add 20 mL of ultra-dry DMF to the single-mouth bottle and bubble for 30 minutes; add azobisisobutyronitrile (AIBN) to the Shrek bottle, replace nitrogen gas three times, transfer the bubbled DMF to the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (styrene) to the Shrek bottle, wherein the molar ratio of monomer A':monomer B' is 1:5; the molar ratio of AIBN:(monomer A'+monomer B') is 1:10; bubble nitrogen gas through the above reaction system for 30 minutes, and then react at 90°C for 24 hours; after the reaction is completed, cool to room temperature, add the product system dropwise into deionized water, precipitate a white solid, filter by suction, take the filter cake and dissolve it in DMF, then add deionized water, filter by suction, and freeze-dry the filter cake to obtain a white solid (i.e., matrix polymer, denoted as M5);

[0107] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:5;

[0108] (2-1) mixing the matrix polymer and polyvinylidene fluoride with a solvent (DMF), and stirring at 60° C. for 3 h to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:10;

[0109] (2-2) Using a 500 μm coating applicator, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.5-2.5 μm, porosity of 26%);

[0110] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The gel polymer electrolyte was prepared by mixing the LiPF6 solution (the solvent was ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a weight ratio of 1:1:1) for 24 hours to obtain a gel polymer electrolyte (denoted as P5).

[0111] Example 6

[0112] (1) Drying a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cooling by vacuum; replacing nitrogen gas in the single-mouth bottle three times, and adding 20 mL of ultra-dry DMF to the single-mouth bottle, and bubbling for 30 minutes; adding azobisisobutyronitrile (AIBN) to the Shrek bottle, replacing nitrogen gas three times, and transferring the above-bubbled DMF to the Shrek bottle, and then adding monomer A' (ethyl methacrylate) and monomer B' (α-methylstyrene) to the Shrek bottle, wherein monomer A The molar ratio of monomer A': monomer B' is 1:5; the molar ratio of AIBN: (monomer A' + monomer B') is 1:10; nitrogen gas is bubbled in the above reaction system for 30 minutes, and then reacted at 90°C for 24 hours; after the reaction is completed, the product system is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, which is filtered by suction, and the filter cake is dissolved in DMF, and then deionized water is added, filtered by suction, and the filter cake is freeze-dried to obtain a white solid (i.e., the matrix polymer, denoted as M6);

[0113] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:5;

[0114] (2-1) mixing the matrix polymer and polyvinylidene fluoride with a solvent (DMF), and stirring at 60° C. for 3 h to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:10;

[0115] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size 0.7-3 μm, porosity 33%);

[0116] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The gel polymer electrolyte was prepared by mixing the LiPF6 solution (the solvent was ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a weight ratio of 1:1:1) for 24 hours to obtain a gel polymer electrolyte (denoted as P6).

[0117] Example 7

[0118] (1) Dry a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cool by vacuuming; replace nitrogen gas in the single-mouth bottle three times, and add 20 mL of ultra-dry DMF to the single-mouth bottle and bubble for 30 minutes; add azobisisobutyronitrile (AIBN) to the Shrek bottle, replace nitrogen gas three times, transfer the bubbled DMF to the Shrek bottle, and then add monomer A' (ethyl methacrylate) and monomer B' (styrene) to the Shrek bottle, wherein the molar ratio of monomer A':monomer B' is 1:5; the molar ratio of AIBN: (monomer A'+monomer B') is 1:10; bubble nitrogen gas through the above reaction system for 30 minutes, and then react at 90°C for 24 hours; after the reaction is completed, cool to room temperature, add the product system dropwise into deionized water, precipitate a white solid, filter by suction, take the filter cake and dissolve it in DMF, then add deionized water, filter by suction, and freeze-dry the filter cake to obtain a white solid (i.e., matrix polymer, the same as M4);

[0119] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:5;

[0120] (2-1) mixing the above-mentioned base polymer and polycarbonate with a solvent (DMF), and stirring at 60° C. for 3 h to obtain a uniform and clear polymer solution; wherein the weight ratio of the base polymer to the polycarbonate is 1:10;

[0121] (2-2) Using a 500 μm coating applicator, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.6-2.8 μm, porosity of 30%);

[0122] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 24 hours in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as P7).

[0123] Example 8

[0124] (1) Dry a 50 mL Shrek bottle and a 25 mL single-mouth bottle for 30 minutes and cool by vacuuming; replace nitrogen gas in the single-mouth bottle three times, and add 20 mL of ultra-dry DMF to the single-mouth bottle and bubble for 30 minutes; add azobisisobutyronitrile (AIBN) to the Shrek bottle, replace nitrogen gas three times, transfer the bubbled DMF to the Shrek bottle, and then add monomer A' (ethyl methacrylate) and monomer B' (styrene) to the Shrek bottle, wherein the molar ratio of monomer A':monomer B' is 1:5; the molar ratio of AIBN: (monomer A'+monomer B') is 1:10; bubble nitrogen gas through the above reaction system for 30 minutes, and then react at 90°C for 24 hours; after the reaction is completed, cool to room temperature, add the product system dropwise into deionized water, precipitate a white solid, filter by suction, take the filter cake and dissolve it in DMF, then add deionized water, filter by suction, and freeze-dry the filter cake to obtain a white solid (i.e., matrix polymer, the same as M4);

[0125] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:5;

[0126] (2-1) mixing the matrix polymer and polyvinylidene fluoride with a solvent (DMF), and stirring at 60° C. for 3 h to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:8;

[0127] (2-2) Using a 500 μm coating applicator, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 10 min, then heated on a heating plate at 60° C. for 5 h, and then dried in a vacuum drying oven at 80° C. for 12 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.9-2.5 μm, porosity of 28%);

[0128] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The gel polymer electrolyte was prepared by mixing the LiPF6 solution (the solvent was ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a weight ratio of 1:1:1) for 24 hours to obtain a gel polymer electrolyte (denoted as P8).

[0129] Comparative Example 1

[0130] The method of Example 4 is followed, except that in step (1), the molar ratio of monomer A':monomer B' is 1:0.005, so that the structural unit in the obtained matrix polymer (denoted as DM1) Structural unit The molar ratio of is 1:0.005. The other steps and conditions are the same as those in Example 4 to obtain a gel polymer electrolyte (denoted as D1).

[0131] Comparative Example 2

[0132] The method of Example 4 is followed, except that in step (1), monomer B' is replaced by an equimolar amount of monomer C' (polyurethane) to obtain a matrix polymer (denoted as DM2). The other steps and conditions are the same as those of Example 4 to obtain a gel polymer electrolyte (denoted as D2).

[0133] Comparative Example 3

[0134] The method of Example 4 is followed, except that polyvinylidene fluoride is not added in step (2-1), that is, no modified polymer is used. The other steps and conditions are the same as those of Example 4, to obtain a gel polymer electrolyte (denoted as D3).

[0135] Test Case

[0136] 1. Mechanical properties test

[0137] The matrix polymers M1-M6 and DM1-DM2 prepared in Examples 1-6 and Comparative Examples 1-2 were cut into strip specimens with a length of 10 mm and a width of 10 cm, respectively. The fracture stress of each specimen was tested using an electronic multifunctional tensile tester (Shenzhen Sansi Zongheng UTM 6000). The results are shown in Table 1.

[0138] Table 1

[0139] Test subjects Fracture stress / MPa M1 1.29 M2 1.32 M3 1.02 M4 2.50 M5 2.12 M6 1.98 DM1 0.98 DM2 0.68

[0140] As can be seen from Table 1, the polymer bodies M1-M6 contained in the gel polymer electrolyte provided by the present invention have relatively high fracture stress, which can make the gel polymer electrolyte have suitable mechanical strength, while the fracture stress of the polymer bodies DM1-DM2 prepared in Comparative Examples 1 and 2 is relatively low.

[0141] 2. Room temperature ionic conductivity test

[0142] The room temperature ionic conductivity test was performed on the gel polymer electrolytes P1-P8 and D1-D3 prepared in Examples 1-8 and Comparative Examples 1-3. The test method is as follows:

[0143] P1-P8, D1-D3 and stainless steel sheet (SS) were assembled into SS / gel polymer electrolyte / SS blocking cells. The electrochemical impedance spectroscopy (EIS) of the cells was tested at room temperature (25°C), and the ionic conductivity of the gel polymer electrolyte was calculated by the following formula (1):

[0144] δ=l / (Rb×A) Formula (1)

[0145] Where δ is the ionic conductivity of the gel polymer electrolyte (unit: mS·cm -1 ), l is the thickness of the gel polymer electrolyte (unit: cm), Rb is the impedance measured by EIS (unit: Ω), and A is the contact area between the blocking electrode (stainless steel sheet) and the gel polymer electrolyte (unit: cm 2 ). The results are shown in Table 2.

[0146] Table 2

[0147]

[0148]

[0149] As shown in Table 2, the gel polymer electrolytes P1-P8 provided by the present invention have high ionic conductivity at room temperature, and the ionic conductivity can be greater than 1.4 mS·cm under the above test conditions. -1 , the highest reached 5.62mS·cm -1 , and after being assembled into a battery, the battery can have excellent rate performance and long cycle stability at a large rate.

[0150] 3. Cycle stability test

[0151] The gel polymer electrolytes P1-P8 and D1-D3 prepared in the above Examples 1-8 and Comparative Examples 1-3 were respectively assembled with the positive electrode and the negative electrode into lithium ion batteries (respectively denoted as B1-B8 and DB1-DB3), wherein the active material in the positive electrode was LiFePO4 and the negative electrode was a lithium metal. The above batteries B1-B8 and DB1-DB3 were tested for capacity retention at 25°C under 3C charge and discharge cycles for 200 cycles. The results are shown in Table 3.

[0152] Table 3

[0153] Test subjects Capacity retention rate (200 cycles) B1 98.3% B2 84.5% B3 88.6% B4 90.1% B5 92.5% B6 77.6% B7 85.3% B8 93.8% DB1 70.2% DB2 72.3% DB3 75.1%

[0154] As can be seen from Table 3, the gel polymer electrolytes P1-P8 provided by the present invention can make the battery have excellent cycle stability. Under the above test conditions, the capacity retention rate of batteries B1-B8 after 200 cycles can be greater than 77%, and can reach up to 98.3%. D1-D3 does not meet the composition of the gel polymer electrolyte of the present invention, and the cycle stability of batteries DB1-DB3 is not as good as B1-B8.

[0155] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A gel polymer electrolyte comprising: A polymer body, and an electrolyte salt solution impregnated in the polymer body; the polymer body contains a base polymer and a modified polymer; Wherein, the base polymer contains a structural unit A represented by formula (I) and a structural unit B represented by formula (II); In formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C4 alkyl group; R3 and R4 are each independently selected from a C1-C4 alkyl group; In formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C4 alkyl group; The molar ratio of structural unit A:structural unit B is 1:(0.01-25).

2. The gel polymer electrolyte according to claim 1, wherein In formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C2 alkyl group; R3 and R4 are each independently selected from a C1-C2 alkyl group; and / or, in formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C2 alkyl group; And / or, the molar ratio of structural unit A:structural unit B is 1:(0.5-1).

3. The gel polymer electrolyte according to claim 1 or 2, wherein: The weight ratio of the base polymer to the modified polymer is 1:(0.1-10), preferably 1:(0.5-1).

4. The gel polymer electrolyte according to any one of claims 1 to 3, wherein the modified polymer is selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyester terephthalates, polyethers, polyimides, polyacrylonitrile, nylon and cellulose, preferably at least one of polyolefins, polysulfonates and polyimides; And / or, the electrolyte salt is selected from at least one of zinc salt, lithium salt, sodium salt, potassium salt, calcium salt, magnesium salt and aluminum salt.

5. A method for preparing a gel polymer electrolyte, comprising: (1) polymerizing monomer A' and monomer B' to obtain a matrix polymer; (2) blending the base polymer and the modified polymer to form a film to obtain a polymer film; (3) plasticizing and swelling the polymer film with an electrolyte salt solution to obtain a gel polymer electrolyte; Wherein, the monomer A' has a structure shown in formula (III), and the monomer B' has a structural unit shown in formula (IV); In formula (III), R1' and R2' are each independently selected from hydrogen or a C1-C4 alkyl group; R3' and R4' are each independently selected from a C1-C4 alkyl group; In formula (IV), R5', R6', and R7' are each independently selected from hydrogen or a C1-C4 alkyl group; The molar ratio of the monomer A':monomer B' is 1:(0.01-25).

6. The method according to claim 5, wherein: In step (1), the polymerization reaction conditions include: temperature of 50-90° C., time of 1-24 h; and / or, in step (2), the weight ratio of the base polymer to the modified polymer is 1:(0.1-10), preferably 1:(0.5-1); And / or, in step (3), the conditions for plasticizing and swelling include: temperature of 0-30°C and time of 1 min-24 h.

7. The method according to claim 5 or 6, wherein: The modified polymer is selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyester terephthalates, polyethers, polyimides, polyacrylonitrile, nylon and cellulose, preferably at least one of polyolefins, polysulfonates and polyimides.

8. The method according to any one of claims 5 to 7, wherein: The electrolyte salt is selected from at least one of zinc salt, lithium salt, sodium salt, potassium salt, calcium salt, magnesium salt and aluminum salt; And / or, the salt concentration in the electrolyte salt solution is 0.1-50 mol / L.

9. A gel polymer electrolyte prepared by the method according to any one of claims 5 to 7.

10. A battery comprising the gel polymer electrolyte according to any one of claims 1 to 4 and 9.